PENGARUH PENGUASAAN GAYA BAHASA FIGURATIF TERHADAP KEMAMPUAN MENGAPRESIASI CERITA PENDEK PADA SISWA KELAS X SMA HASANUDDIN GOWA - Rahmi, Nur (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
This study aimed to determine the effect of figurative language style of the ability of students to appreciate the short story. This study was classified as experimental research. Research data obtained through test techniques. This study population was all students of class X SMA Hasanuddin of Gowa. Based on the analysis and discussion of the results of this study concluded that the results of the average score of the ability to appreciate the short story class X SMA Hasanuddin of Gowa without fiiguratif stylistic mastery on the posttest 13.2 in the low category with the thoroughness of the number of students 20%. The results of the average score of the ability to appreciate the short story class X SMA Hasanuddin of Gowa with mastery of figurative language style on the posttest 29.6 and higher are categorized by the number of students 85% completeness. Mastery of figurative language style effect in appreciating short stories high school Class X students Hasanuddin of Gowa. The role of mastery of this style of figurative language seems clearly based on the calculation of Paired Samples Test t-test which showed that as many as 9,752 t count > t table value of 2.09. This shows that the proposed research hypothesis is accepted.